2017
DOI: 10.1186/s40001-017-0291-8
|View full text |Cite
|
Sign up to set email alerts
|

The use of 5-fluorouracil-loaded nanobubbles combined with low-frequency ultrasound to treat hepatocellular carcinoma in nude mice

Abstract: ObjectiveThis study aimed to investigate the therapeutic effects of 5-fluorouracil (5-FU)-loaded nanobubbles irradiated with low-intensity, low-frequency ultrasound in nude mice with hepatocellular carcinoma (HCC).MethodsA transplanted tumor model of HCC in nude mice was established in 40 mice, which were then randomly divided equally into four groups: group A (saline), group B (5-FU-loaded nanobubbles), group C (5-FU-loaded nanobubbles with non-low-frequency ultrasound), and group D (5-FU-loaded nanobubbles w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Tumor cell lines derived from different tissues can affect ultrasound sonoporation efficiency, and cell membrane permeability can be safely and effectively increased through optimizing exposure parameters [18]. Moreover, unfavorable irradiation parameters can cause cell death [19]. Therefore, it is of great significance to screen the optimal parameters of low frequency ultrasound-mediated gene transfection.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cell lines derived from different tissues can affect ultrasound sonoporation efficiency, and cell membrane permeability can be safely and effectively increased through optimizing exposure parameters [18]. Moreover, unfavorable irradiation parameters can cause cell death [19]. Therefore, it is of great significance to screen the optimal parameters of low frequency ultrasound-mediated gene transfection.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al (2018) reported that low-frequency ultrasound combined with multifunctional FOXA1 porphyrin-loaded microbubbles significantly increased the local accumulation of porphyrin and siRNA by ultrasound-induced acoustic perforation, and had a good therapeutic effect on estrogen-dependent ER + breast cancer. Li et al (2017) reported that 5-FU polylactic acid nanobubbles irradiated by low-frequency ultrasound could further improve drug targeting and effectively inhibit the growth of hepatocellular carcinoma in nude mice.…”
Section: Mediating Targeted Tumor Drug Therapy Improving the Efficacmentioning
confidence: 99%
“…Compared to traditional microbubbles, nanosized particles can cross the capillary wall more easily and hence can be delivered to the target site more efficiently. NBs have been used in the study of targeted therapy, such as 5-fluorouracil-loaded NBs tested for use in hepatocellular carcinoma [2]. Shen et al recently used ultrasound-mediated NBs to deliver resveratrol to nucleus pulposus cells [3], and NBs have also been used in the treatment of breast cancer [4].…”
Section: Introductionmentioning
confidence: 99%